2020
DOI: 10.1002/er.6051
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the bandgap on the photovoltaic‐thermoelectric hybrid system

Abstract: Summary The photovoltaic‐thermoelectric hybrid system (PVTE) is less sensitive to the photon wavelength than the pure PV system. This phenomenon can make the PVTE to be a good method of obtaining electrical energy from solar energy. A challenge of this system is how to distribute the energy in the working process. To solve this problem, this paper establishes a thermodynamic model to study the energy matching mechanism of the hybrid system. The influence of dynamic solar radiation has been considered in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…They concluded that employing the more efficient TEG, PCM and TIM with excellent thermal properties while loading high water-cooling rate of flow will prompt the concentrated PV-TEG system to generate more electricity. Recently, Zhang et al established a thermodynamic model to study the energy matching mechanism of PV/PCM/TEG system [120]. They found that the relationship between the efficiency of system and the PV cell bandgap looks like a "reverse U" (rises first and falls later) with considering dynamic solar radiation.…”
Section: Pv-teg-pcmmentioning
confidence: 99%
“…They concluded that employing the more efficient TEG, PCM and TIM with excellent thermal properties while loading high water-cooling rate of flow will prompt the concentrated PV-TEG system to generate more electricity. Recently, Zhang et al established a thermodynamic model to study the energy matching mechanism of PV/PCM/TEG system [120]. They found that the relationship between the efficiency of system and the PV cell bandgap looks like a "reverse U" (rises first and falls later) with considering dynamic solar radiation.…”
Section: Pv-teg-pcmmentioning
confidence: 99%
“…Therein, a change in the temperature of the PV part causes a nonlinear tradeoff of output powers in the TE and PV parts, where we want to know how optimized output can be obtained. Until now, numerical simulations for various configurations have been reported, [2][3][4][5][6][7][8][9][10][11][12][13][14][21][22][23][24][25][26][27] and several experimental reports have indeed demonstrated superior outputs of PVTE hybrid tandems over their original PV outputs. [15][16][17][18][19] PVTE tandems are classified into four-and two-terminal types and the latter is further classified into series and parallel types according to electrical connections (Fig.…”
mentioning
confidence: 99%
“…Ayrıca ideal tasarım koşullarında önerilen sistemin referans sisteme göre %4,47 daha fazla enerji üretebileceği bildirilmiştir. PV, PV-TE ve PV-FDM-TE sistemlerin karşılaştırılması Zhang vd.,[64] tarafından incelenmiştir. Önerilen PV-FDM-TE sistemde faz değiştiren malzemenin erime sıcaklığı göz önünde bulundurularak PV bant aralığının etkisi analiz edilmiştir.…”
unclassified